Seneca valley virus VP4 protein regulates the transcription of different cytokines in vitro - Leng, Chaoliang; Ge, Yu; Ruan, Mengfan; Zhao, Wenxiao; Yang, Ximei; Gao, Sainan; Zhai, Hongyue; Li, Dandan; Rao, Dan; Dong, Jianguo (Frontiers in Veterinary Science, 2025)
To understand the effect of Seneca valley virus (SVV) VP4 protein on innate immune factors, the VP4 gene was cloned into the pEGFP-C1 expression plasmid to construct the pEGFP-C1-VP4 recombinant plasmid. After the recombinant plasmid was transfected into 293 T cells, the cell fluid was collected 24 h after transfection for western blot assay to identify the correctness of VP4 protein expression. Cell culture medium was collected from un-transfected and transfected cells at three time points (12, 24, and 36 h). mRNA expression levels of cytokines (IL-1α, IL-1β, CCL-2, CCL-5, CXCL-10, and TNF-α) at three time points were detected by quantitative real-time PCR (qPCR) method, and relative quantitative analysis was performed by 2-ΔΔCt method. The results indicated that the expressed SVV VP4 protein exhibits good activity in vitro. Overexpression of the VP4 protein could significantly promote the transcription of IL-1α and IL-1β at 24 and 36 h. In addition, the transcription of CCL-2 and CCL-5 was also significantly promoted at 36 h, whereas the transcription of CCL-10 was significantly promoted only at 12 h. The TNF-α transcription was significantly inhibited at all the three time points. This study provides an important basis for the pathogenic mechanism of SVV and vaccine design in the future.